2019
DOI: 10.21873/anticanres.13455
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Elevated Postoperative Carbohydrate Antigen 19-9 Levels in Patients With Resected Pancreatic Cancer

Abstract: Aim: In this study, we investigated the clinical significance of postoperative serum carbohydrate antigen (CA) 19-9 in patients with pancreatic ductal carcinoma (PDAC). Patients and Methods: A series of 116 patients with macroscopically curative PDAC resection was retrospectively evaluated. The cut-off level for elevated postoperative CA 19-9 was 37 U/ml. Results: Patients with high postoperative CA19-9 levels had a significantly poorer prognosis than patients with normal postoperative CA19-9 levels, as reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Evaluation of preoperative CA199 is positively associated with tumor resectability and postoperative prognosis (14,16,44,45). Furthermore, postoperative CA199 levels have been reported to predict OS and disease-free survival following cancer resection and adjuvant chemotherapy (45)(46)(47)(48)(49). Consistent with the results from the present study, a previous report demonstrated that CA199 can predict the prognosis of patients with resected pancreatic adenocarcinoma when combined with PLR (45).…”
Section: -Year Os 3-year Os 5-year Os ------------------------------supporting
confidence: 90%
“…Evaluation of preoperative CA199 is positively associated with tumor resectability and postoperative prognosis (14,16,44,45). Furthermore, postoperative CA199 levels have been reported to predict OS and disease-free survival following cancer resection and adjuvant chemotherapy (45)(46)(47)(48)(49). Consistent with the results from the present study, a previous report demonstrated that CA199 can predict the prognosis of patients with resected pancreatic adenocarcinoma when combined with PLR (45).…”
Section: -Year Os 3-year Os 5-year Os ------------------------------supporting
confidence: 90%
“…CA19-9 is the most effective indicator for the diagnosis and follow-up of patients with pancreatic cancer ( 38 ). A CA19-9 level > 150 U/ml is highly correlated to pancreatic cancer ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…ROC analysis showed that the AUC of IgG4 level before treatment, Tbil level before treatment, IgG4/Tbil before treatment, a combination of IgG4 and Tbil before treatment, and combination of IgG4, Tbil, and IgG4/Tbil before treatment was 0.915, 0.707, 0.919, 0.921, and 0.924, respectively (Figure 1, Table 3), indicating that all of these indicators had a high diagnostic value for AIP, among which the combination of IgG4, Tbil, and IgG4/Tbil before treatment had the highest diagnostic value. CA19-9 is the most effective indicator for the diagnosis and follow-up of patients with pancreatic cancer (38). A CA19-9 level > 150 U/ml is highly correlated to pancreatic cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…CA19-9 is the only peripheral blood-based biomarker used to diagnose PDAC, but some studies (26,27) have concluded that this marker is not tumor-specific and is not suitable as a diagnostic biomarker for early metastases. However, some studies (28)(29)(30) have shown a possible correlation between CA19-9 ≥400 U/mL and hepatic metastasis. Meanwhile, other studies (27,31,32) have shown that the presence of circulating tumor cells (CTCs) in portal blood is associated with a higher rate of liver metastasis after resection of the primary tumor.…”
Section: Discussionmentioning
confidence: 99%